Distribution Pattern and Population Density of Spodoptera frugiperda (Lepidoptera: Noctuidae) in Corn Fields in the Tanggunggunung Hills, Tulungagung Regency - Tito Ridho Nugroho; Wiwin Windriyanti; Noni Rahmadhini (Universitas Labuhanbatu, 2025)
Background: Corn is an important commodity in Tulungagung Regency; however, infestations of Spodoptera frugiperda have caused substantial yield losses, particularly during the vegetative growth stage, with reported damage levels reaching 20–70% depending on infestation intensity. Understanding the population density and spatial distribution of this pest under local agroecosystem conditions is therefore essential for developing effective control strategies. This study aimed to analyze the population density, distribution pattern, and environmental relationships of S. frugiperda on corn plants in the hilly area of Tanggunggunung, Tulungagung Regency. Methodology: The research was conducted on corn plants aged 15 to 45 days post-planting at two distinct locations: Ngrejo Village (approximately 110 meters above sea level) and Jengglungharjo Village (approximately 145 meters above sea level), each encompassing an area of 25 square meters. A two-dimensional sampling method was employed, utilizing 10 fixed observation plots per field, with observations occurring every three days. The variables observed included pest population density, symptoms of pest attack, and abiotic environmental factors such as temperature and humidity. Distribution patterns were analyzed using the Morisita index and the degree of Morisita (Ip), while the relationships between pest populations and environmental factors were examined through Pearson’s correlation analysis. Findings: The population of S. frugiperda in Ngrejo village exhibited a random distribution pattern (Id= 1.016; Ip= 0.004), whereas in Jengglungharjo village, it demonstrated a tendency towards clustering (Id = 0.211; Ip= 0.456). The density of the pest population showed a strong positive correlation with temperature (r= 0.799 to 0.702) and a negative correlation with humidity (r= −0.661 to −0.423). Contribution: Microclimatic conditions play a key role in shaping the spatial distribution and population density of S. frugiperda, highlighting the importance of site-specific, ecology-based pest management to improve corn productivity in hilly agroecosystems